Managing jelly seed formation in mango - Singh, V K (Indian Horticulture, 2018)
Jelly seed formation is one of serious problems in mango, particularly in northern belt, which is characterised by loosening of pulp, jelly formation, off-flavour and dull colour around stone, resulting in reduction of shelf-life of fruits. Dashehari, the choicest variety of north India, is highly susceptible to this disorder. The affected fruits look like normal from the outside but after slicing give an unpleasant appearance and become unfit for consumption. In jelly seed affected fruits, besides high ethylene evolution, pectin hydrolases is found higher as compared to healthy fruits. Affected tissue have low Ca, K and antioxidant capacity with higher N, P, Fe and Zn. There is no significant difference in Mg, Cu and Mn in both types of tissue. The physiological status of seed is also associated with development of jellyÂ seed in mango. To minimise its incidence, cost-effective method is developed involving application of black plastic mulch (100 Î¼ thick) during October-November and foliar spraying of dihydrated calcium chloride (2.0%), potassium sulphate (1.0%) one month before harvesting of fruits along with application of 150 g borax per tree in soil at the time of mulching.